Asymmetrically Reconstructed Optical OFDM for Visible Light Communications - Jindan Xu; Wei Xu; Hua Zhang; Xiaohu You (IEEE Photonics Journal)
In conventional optical orthogonal frequency-division multiplexing (OOFDM) systems, such as pulse-amplitude-modulated discrete multitone (PAM-DMT) and asymmetrically clipped optical OFDM (ACO-OFDM), half of the time-domain transmitted signals carry meaningful information, while the other half are set at zero after asymmetric clipping. By specifically exploiting the asymmetric structure of OOFDM such as PAM-DMT and ACO-OFDM, we present a new framework for implementing OOFDM with enhanced performance in terms of both bit error rate (BER) and peak-to-average power ratio (PAPR). The proposed scheme introduces asymmetric signal reconstruction, instead of direct clipping, in the time domain before transmission. The designed asymmetric reconstruction refines the time-domain statistics of the OOFDM signals by constructively exploiting zero-padded signal positions in conventional OOFDMs. This way, the PAPR of the reconstructed OOFDM signals is effectively reduced. For receivers, to recover the received signals precisely, we further develop an optimal maximum a posteriori detection method, along with an efficient simplified method. Simulation results validate that the proposed scheme enhances the BER performance compared with conventional OOFDMs under both an ideal and a dispersive visible light communication (VLC) channel via our prototype. Specifically, under an ideal additive white Gaussian noise channel, an approximately 4-dB gain is achieved at the BER of $10^{-2}$ , along with a 2.5-dB lower PAPR constraint. While under the real dispersive channel, our test shows about 6-dB gain in BER performance.